NURSING CARE FOR HYPEREMESIS GRAVIDARUM CLIENTS WITH A STUDY FOCUS ON THE MANAGEMENT OF NUTRITIONAL IMBALANCE - Kamariah, Kamariah; Savage , Eileen (Lux Mensana: Journal of Scientific Health, 2024)
Introduction: Hyperemesis gravidarum is a condition where sufferers experienceexcessive nausea and vomiting, more than 10 times in 24 hours, thus disrupting their healthand daily work. One of the complications that occurs in hyperemesis gravidarum isnutritional imbalance less than the body's needs . Therefore, it is important to manageHyperemesis Gravidarum by changing the pattern nutrition. The author aims to discuss andexamine the application of nursing care with a focus on studying nutritional imbalancesless than body requirements in clients with hyperemesis gravidarum. Methods: Themethod used is a descriptive method, namely describing managed cases systematically.Results & Analysis: The results of the research were obtained during 3x24 hour nursingcare, the problem of nutritional needs for clients with hyperemesis gravidarum could beresolved in accordance with the established criteria with the results of the implementationcarried out having a response that showed the client's development. Discussion: nutritionalneeds for clients with hyperemesis gravidarum are very important, therefore it is hoped thatnurses or hospitals can pay more attention to the patient's nutritional status according toneeds and improve counseling services for pregnant women to prevent this incident